2017
DOI: 10.1002/jcla.22331
|View full text |Cite
|
Sign up to set email alerts
|

Association of GPIa and COX‐2 gene polymorphism with aspirin resistance

Abstract: ObjectiveThis study aimed to explore the association between GPIa, COX‐2 gene polymorphisms and aspirin resistance in the ischemic stroke patients from the southern part of Jiangsu province.MethodsIn all, 97 patients with acute ischemic stroke were enrolled in the study. GPIa gene polymorphism at 807C>T (rsl126643) locus and COX‐2 gene polymorphism at ‐765G>C (rs20417) locus were genotyped by PCR pyrosequencing technology. Patients were divided into the aspirin sensitivity (AS) group and aspirin resistance (AR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 20 publications
0
9
0
1
Order By: Relevance
“…The second limitation is related to the size of the studied population. It seems to be large enough compared with other studies in the field [ 21 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. However, clarifying the genetic background of aspirin treatment failure, which is affected by numerous clinical parameters and studied SNPs, requires further studies including larger and more clinically uniform cohorts of patients.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The second limitation is related to the size of the studied population. It seems to be large enough compared with other studies in the field [ 21 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. However, clarifying the genetic background of aspirin treatment failure, which is affected by numerous clinical parameters and studied SNPs, requires further studies including larger and more clinically uniform cohorts of patients.…”
Section: Discussionmentioning
confidence: 92%
“…The SNPs were selected based on the literature data. All of them are involved in platelet activation and aggregation, and their contribution to aspirin resistance is discussed in numerous studies [ 6 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. We evaluated the distribution of 16 genetic markers in the AS and AR groups in a cohort of 461 patients with acute ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies focusing on the polymorphism of ITGA2 C807T gene that encodes the GPIa collagen receptor have proved its correlation with aspirin resistance. A study of Han Chinese patients with acute ischemic stroke shows that the T allele significantly correlates with aspirin resistance (OR 4.86) [7]. Similarly, a metaanalysis reveals that rs1126643 (C807T) polymorphism becomes the genetic variation associated with aspirin insensitivity [8], risk of ischemic stroke among the Asian populations [9], and risk of elevated levels of serum cholesterol [10].…”
Section: Introductionmentioning
confidence: 99%
“…Despite adequate aspirin therapy, 6.2-57% patients still experience cardiovascular events, the phenomenon named as aspirin resistance (AR) [2]. Researchers have reported that genetic variability in cyclooxygenase-2 (COX-2)-765G/C (rs20417) affect aspirin response with cardiovascular disease and could be used as specific genetic marker of AR [3,4]. Therefore, it is crucial to prescreen patients for their genotypes before prescribing aspirin to facilitate target therapy and decreasing the side effects associated with prolonged administration.…”
Section: Introductionmentioning
confidence: 99%